2015
DOI: 10.1038/jcbfm.2015.176
|View full text |Cite
|
Sign up to set email alerts
|

MR Derived Volumetric Flow Rate Waveforms of Internal Carotid Artery in Patients Treated for Unruptured Intracranial Aneurysms by Flow Diversion Technique

Abstract: Little is known about the hemodynamic disturbances induced by the cerebral aneurysms in the parent artery and the effect of flow diverter stents (FDS) on these latter. A better understanding of the aneurysm-parent vessel complex relationship may aid our understanding of this disease and to optimize its treatment. The ability of volumetric flow rate (VFR) waveform to reflect the arterial compliance modifications is well known. By analyzing the VFR waveform and the pulsatility in the parent vessel, this study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Recent studies found that pulsatile flow is affected by physiological and pathological vascular geometry when investigating in a proximal-distal approach. 13,30,31 An important finding in this study was that the pulsatile flow that reaches distal arterial segments was augmented with age. Firstly, the PIs in large proximal arteries were increased in elderly (Table 2) and secondly the dampening capacity of the cerebral arteries was more efficient in the young group for all cerebral arterial segments (Table 3).…”
Section: Dampening Of Pulsatile Flow In the Cerebral Arteriesmentioning
confidence: 69%
“…Recent studies found that pulsatile flow is affected by physiological and pathological vascular geometry when investigating in a proximal-distal approach. 13,30,31 An important finding in this study was that the pulsatile flow that reaches distal arterial segments was augmented with age. Firstly, the PIs in large proximal arteries were increased in elderly (Table 2) and secondly the dampening capacity of the cerebral arteries was more efficient in the young group for all cerebral arterial segments (Table 3).…”
Section: Dampening Of Pulsatile Flow In the Cerebral Arteriesmentioning
confidence: 69%
“…Reliable blood flow measurements in intracranial vessels are crucial for the understanding and management of neurovascular diseases. Indeed, hemodynamic modifications caused by Alzheimer's disease (43), aging (40,44) or IAs flow diverter treatment (6,7) were shown recently using 2D-or 3D-PCMRI. One of the most promising clinical applications of 3D-PCMRI concerns the assessment and treatment of brain AVM.…”
Section: Discussionmentioning
confidence: 99%
“…Several neurovascular pathologies are associated with alterations of blood flow dynamics such as arteriovenous malformation (AVM) (1)(2)(3)(4), arterial stenosis (5), or intracranial aneurysms (IAs) (5)(6)(7). These serious pathologies require a full work-up to decide the best management.…”
Section: Introductionmentioning
confidence: 99%
“…32 In the context of flow-diversion treatment, only a few PCMR investigations have been reported. The hemodynamic changes in the parent vessel were measured in patients with 2D-PCMR by Eker et al 7 and MacDonald et al 33 Sindeev et al 20 used 4D-PCMR in 3 patient-specific models and found flow reductions of 89% and 30%-50% for fast and delayed thrombosis outcomes, respectively. Karmonik et al 21 used a combination of in vitro experiments and the measurements of 3 patients, but these were not associated with occlusion times, findings similar to those of Pereira et al 22 This limited literature can probably be attributed to the inherent limitations of 4D-PCMR related to data acquisition: long scan duration; coarse spatial resolution regarding the size of the IA; the unique velocity encoding (VENC) that cannot cover the large range of involved velocities; and the low temporal resolution, which smooths out the peak systolic velocities.…”
Section: Pcmr Measurements and Flow Diversionmentioning
confidence: 99%
“…[1][2][3][4] The high density of stent struts across the IA neck dampens the intrasaccular flow and promotes a progressive thrombosis of the cavity to ultimately exclude the aneurysm from the circulation. 5,6 FDSs also have other advantages such as vessel wall remodeling of the parent artery, often altered in large-neck ICA aneurysms, 7 as well as the improvement of outcomes for symptomatic lesions due to the progressive decompression of surrounding tissues as the aneurysm shrinks. 8 In addition, compared with other endovascular procedures, FDS implantation yields a higher rate of complete and permanent aneurysm exclusion, considering both residual and complete recanalization.…”
mentioning
confidence: 99%